Glutathione supplementation improves fat graft survival by inhibiting ferroptosis via the SLC7A11/GPX4 axis - Zehua Li; Jinqiang Lu; Zhiqin Dong; Jiaji Liang; Shenghong Li; Wenwen Han; Taixing Cui; Hongwei Liu (Stem Cell Research & Therapy, 2024)
Abstract Background Autologous fat grafting is hampered by unpredictable graft survival, which is potentially regulated by ferroptosis. Glutathione (GSH), a powerful antioxidant used in tissue preservation, has ferroptosis-regulating activity; however, its effects on fat grafts are unclear. This study investigated the effects and mechanisms of GSH in fat graft survival. Methods Human lipoaspirates were transplanted subcutaneously into the backs of normal saline-treated (control) or GSH-treated nude mice. Graft survival was evaluated by magnetic resonance imaging and histology. RNA sequencing was performed to identify differentially expressed genes and enriched pathways. GSH activity was evaluated in vitro using an oxygen and glucose deprivation (OGD) model of adipose-derived stem cells. Results Compared with control group, GSH induced better outcomes, including superior graft retention, appearance, and histological structures. RNA sequencing suggested enhanced negative regulation of ferroptosis in the GSH-treated grafts, which showed reduced lipid peroxides, better mitochondrial ultrastructure, and SLC7A11/GPX4 axis activation. In vitro, OGD-induced ferroptosis was ameliorated by GSH, which restored cell proliferation, reduced oxidative stress, and upregulated ferroptosis defense factors. Conclusions Our study confirms that ferroptosis participates in regulating fat graft survival and that GSH exerts a protective effect by inhibiting ferroptosis. GSH-assisted lipotransfer is a promising therapeutic strategy for future clinical application.